A new on-table colonic irrigation device- results of a pilot study - Sabaratnam, V.Y.; Deen, K.I.; Kim, J.H. (The College of Surgeons of Sri Lanka and SAARC Surgical Care Society, 2003)
INTRODUCTION: Management of left colon obstruction either by primary anastomosis or by diversion almost always requires decompression and lavage of the colon. This will facilitate colonic mobilization primary anastomosis, delivery of stoma without contamination and tension free abdominal wound closure. Objective: To examine the results of a new devise that enables on-table he ability to perform concomitant colonoscopy. METHODS: 8 patients (5 males, median age 44 years; range 23 to 78 years) underwent resection of left colon cancer (I), recto-sigmoid cancer (3), and rectal cancer (4). Four were obstructing tumours, while in the remaining 4, full bowel preparation with polyethylene glycol was deemed risky hence requiring intraoperative preparation. The device consisted of a screw-on plastic tube (diameter- 35mm), with an inlet valve and a single outlet for faecal effluent. Following complete irrigation. on table colonoscopy was possible through the inlet. Features assessed were extra intestinal faecal leakage, bowel perforation, irrigation time, volume infused and total time taken. RESULTS: There was no technical problem with introduction and securing the device to the bowel wall. Leakage of faeces was not encountered in a single case. Total time taken for irrigation was (median. range) 20 minutes (8-20), colonoscopy time was 8 and 10 minutes respectively in 2 patients who underwent colonoscopy. 5 underwent primary anastomosis whilst 2 underwent Hartmann operation and I had a Paul-Mickulicz procedure. No anastomotic leakages were detected clinically. No faecal contamination was encountered. All were commenced on oral fluids on day 1 after operation, median time to pass flatus was 2 days (1-3) and discharge from the hospital was (median. range) 8 days (6-12). CONCLUSION: This disposable irrigation device guarantees a complete bowel seal during on-table lavage and ensures complete decompression with bowel cleansing, enabling safe anastomosis
Free Papers Abstract, The Annual Sessions of the College of Surgeons of Sri Lanka and SAARC Surgical Care Society,13rd -17th August 2003 Kandy, Sri Lanka
Keywords: Colonic irrigation